Tokyo Church of Christ - Fumihiko Maki (Oz, 1998)
The dual nature of the church, a place for both congregation and contemplation, has always fascinated me. Regardless of the denomination to be served, church design must consider both space and music, elements that transcend the boundaries between religions and serve as a common existential foundation for all.